Effect of Expressive Writing Therapy in Improving Communication in Adolescents - Qurrota A'yu; Zahro Varisna Rohmadani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to determine the effectiveness of expressive writing therapy in improving interpersonal communication skills among junior high school students who experience communication anxiety. The method used is a quasi-experimental design with a one-group pretest-posttest model. The sample consists of 10 students selected based on low communication scores from an initial population of 50 students. The intervention was carried out in four sessions, focusing on emotional awareness, self-value, self-reflection, and communication planning. The results showed a significant increase in communication skills based on paired sample t-test results (p < 0.05). This finding supports that expressive writing can serve as an effective intervention to enhance adolescent communication abilities.